Nicholas Nickleby : a faithful account of the fortunes, misfortunes, uprisings, downfallings and complete career of the Nickleby family - Dickens, Charles, 1812-1870 (Floating Press, 2009)
After Nicholas Nickleby's father dies bankrupt, Nicholas becomes the unhappy ward of his uncle, a moneylender, and survives many adventures before finding happiness.